2008
DOI: 10.2165/0002018-200831120-00006
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Neuropsychiatric Adverse Events in Influenza Patients Treated with Oseltamivir

Abstract: After reports from Japan of neuropsychiatric adverse events (NPAEs) in children taking oseltamivir phosphate (hereafter referred to as oseltamivir [Tamiflu; F. Hoffmann-La Roche Ltd, Basel, Switzerland]) during and after the 2004--5 influenza season, Roche explored possible reasons for the increase in reporting rate and presented regular updates to the US FDA and other regulatory authorities. This review summarizes the results of a comprehensive assessment of the company's own preclinical and clinical studies,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
115
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(124 citation statements)
references
References 32 publications
8
115
1
Order By: Relevance
“…NPAEs have occurred in young patients during relatively early phase after the onset of influenza-like symptoms [[9]]. Furthermore, it was reported that 30% of the abnormal behaviors of pediatric patients occurred within 2 h after the first use of oseltamivir [[9]], which is close to the time of reaching maximum plasma concentrations of oseltamivir and Ro 64-0802 [[6]].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…NPAEs have occurred in young patients during relatively early phase after the onset of influenza-like symptoms [[9]]. Furthermore, it was reported that 30% of the abnormal behaviors of pediatric patients occurred within 2 h after the first use of oseltamivir [[9]], which is close to the time of reaching maximum plasma concentrations of oseltamivir and Ro 64-0802 [[6]].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was reported that 30% of the abnormal behaviors of pediatric patients occurred within 2 h after the first use of oseltamivir [[9]], which is close to the time of reaching maximum plasma concentrations of oseltamivir and Ro 64-0802 [[6]]. It is possible that the immune response leads to the elevation of CNS oseltamivir concentration by increasing BBB permeability and/or plasma oseltamivir concentration.…”
Section: Introductionmentioning
confidence: 99%
“…For one trial, Wang et al56 described study results whereby gastrointestinal symptoms were related to the adverse effects of laninamivir treatment in children. Other AEs, including neuropsychiatric AEs were observed occasionally in influenza patients receiving oseltamivir 57,58. Sudden death was reported as an AE related to oseltamivir 59,60.…”
Section: Resultsmentioning
confidence: 99%
“…43 Despite earlier post-market reports of transient neuropsychiatric events manifested as self-injury or delirium in Japan, 44 more recently, oseltamivir has not been associated with increased risk of neuropsychiatric events. 45 The FDA recommends close monitoring for abnormal behavior in patients treated with oseltamivir. 43 The FDA and CDC also recommend that clinicians and pharmacists pay careful attention to the possibility of dosing errors in young children.…”
Section: Influenza (Last Updated November 6 2013; Last Reviewed Novementioning
confidence: 99%